Embriologija živčevja - Petrovič, Danijel (Medicinski razgledi, 2000)
The notochord and para-axial mesoderm induce the overlying ectoderm to differentiate into the neural plate. Formation of the neural tube begins in the fourth week, when the walls of the neural tube thicken to farm the brain and spinal cord. The neural canal is converted into the ventricular system of the brain and the central canal of the spinal cord. In the fourth week of development, the cranial part of the neural tube shows three protrusions knownas primary brain vesicles the prosencephalon, embryonic mesencephalon andrhombencephalon. The mesenchyma surrounding the neural tube condenses to form a membrane called the primordial membrane, from which the dura mater and the pia-arachnoidea are formed. The cerebrospinal fluid begins to appear in the fifth week. The axtons are non-myelinated at the beginning; nerve myelination begins at about 20 weeks. Initially, the surface of the hemispheres is smooth, but as growth proceeds, sulci and gyri develop.
Keywords: Nervous system; živčevje; embriologija; Embryology; Spinal cord; Ganglia, spinal; Brain; Medulla oblongata; Mesencephalon; Diencephalon; Basal ganglia; Pituitary gland; Telencephalon